Pelatihan Dan Pendampingan Basic Accounting Pada Kelompok Usaha Kripik Pakis Di Dusun Gule Liat Desa Setiling Batukliang Utara Dengan Memanfaatkan Media Mainstream - Pituringsih, Endar; Handajani, Lilik; Sokarina, Ayudia; Ulfa, Pipit Rismayani; Akma, Hidayatul (Jurnal Gema Ngabdi, 2025)
The training and mentoring activities on financial reporting using basic accounting and the utilization of mainstream media were carried out for the Pakis chips business group in Gule Liat Hamlet, Setiling Village, Batukliang Utara District, Central Lombok Regency. The purpose of this program is to provide knowledge and practical skills for the Pakis chips business group in Gule Liat Hamlet, Setiling Village, Batukliang Utara District, Central Lombok Regency regarding basic accounting and mainstream media. It is expected that the group will be able to conduct accurate bookkeeping and record-keeping using proper basic accounting methods. In addition, the training is designed to equip participants with both knowledge and skills in financial reporting and the use of mainstream media, which are expected to foster greater independence in entrepreneurship and ultimately increase income. This training activity is specifically targeted at the Pakis chips business group in Gule Liat Hamlet, Setiling Village, Batukliang Utara District, Central Lombok Regency. The implementation is carried out through the delivery of relevant materials. Another expectation of this activity is that it will serve as a platform for community service, particularly by providing education and training on mainstream media and basic accounting for the Pakis chips business group.